Effects of Curcumin on High Glucose-Induced Epithelial-to-Mesenchymal Transition in Renal Tubular Epithelial Cells Through the TLR4-NF-κB Signaling Pathway - Liu, Xinhui (Diabetes Metab Syndr Obes, 2021)
OBJECTIVE: Diabetic kidney disease (DKD) is a microvascular complication in diabetes mellitus, while tubuloepithelial to mesenchymal transition (EMT) of mature tubular epithelial cells is a key point in the early development and progression of renal interstitial fibrosis. The present study aimed to investigate the protective effects of Curcumin on EMT and fibrosis in cultured normal rat kidney tubular epithelial cell line (NRK-52E). METHODS: By using immunofluorescence staining and Western blot protocols, in vitro experiments were designed to analyze EMT markers, including collagen I and E-cadherin in high glucose (HG) exposed NRK-52E cells and to detect the expression levels of phosphorylated-NF-κB, TLR4 and reactive oxygen species (ROS) after Curcumin pre-treatment. With co-treatment with TAK242, these molecules in the TLR4-NF-κB signaling pathway were further evaluated. RESULTS: Curcumin decreased the HG-induced EMT levels and ROS production in NRK-52E cells. Furthermore, Curcumin was found to inhibit the TLR4-NF-κB signaling activation in HG-induced EMT of NRK-52E cells. CONCLUSION: The present study provides evidence suggesting a novel mechanism that Curcumin exerts the anti-fibrosis effects via inhibiting activation of the TLR4-NF-κB signal pathway and consequently protecting the HG-induced EMT in renal tubular epithelial cells. Thereby, TLR4-NF-κB may be a useful target for therapeutic intervention in DKD.